PENGGUNAAN METODE SQ3R TERHADAP HASIL BELAJAR AKUNTANSI SISWA - Rixaza Rixa Rixala Harahap, Rijal Lubis (JURNAL PENDIDIKAN IPS, 2020)
Learning method is the method used to implement a plan that has been prepared in the form of real and practical activities in order to achieve the learning mission, which is a method chosen by educators to be able to optimize the teaching and learning process that aims so that learning objectives can be expected. Cooperative learning method type SQ3R is a learning method that uses reading strategies by assigning students to read study material carefully. This inspires the writer to apply the SQ3R learning method so that students are required to play an active role, so students will more easily understand the subject matter delivered by the teacher. The formulation of the problem in this study is "Are the learning outcomes of students who learn to use the SQ3R Method higher than the learning outcomes of students who learn to use the Conventional Method. The results of data analysis in this study obtained t count 28,2466 and t table 2,0042 so that tcount> ttable (28,2466 > 2,0042), this shows that the hypothesis that the author has specified in this study is acceptable. That is, the learning outcomes of students who learn using the SQ3R method are higher than the learning outcomes of students who learn using conventional methods. In line with these conclusions, researchers suggested that accounting teachers apply the SQ3R learning method in the teaching and learning process, especially on accounting subjects.